Clinico epidemiological study of blunt abdominal trauma in a tertiary care hospital in north western Himalayas - Malhotra, Parikshit; Sharma, Dhruv; Gupta, Sanjiv; Minhas, S. S. (International Surgery Journal, 2017)
Background: Blunt abdominal trauma (BAT), a common form of trauma, is one of the major causes of morbidity and mortality. The study was aimed at the study of spectrum of injuries to various intra-abdominal organs after blunt trauma and to ascertain cause/mode of BAT in a hospital of hilly locality of Shimla. Methods: A prospective study was designed to conduct in the department of Surgery, IGMC, Shimla, India during the period of one year from 1st June 2005 to 31st May 2006. A total of 30 patients who had sustained BAT with or without other associated injuries were selected. In all patient’s history was taken and detailed physical examination done while concomitant resuscitation was performed. Chest and abdominal radiographs were done in all patients. Results: BAT is a major cause of morbidity and mortality especially in young people in the 11-40 years’ age group. Males are affected more than females. Road traffic accidents are the predominant mode of injury however, a relatively high incidence of blunt abdominal trauma due to falls is observed in a hilly state like ours. Spleen and liver are the two commonly injured organs after blunt abdominal trauma. Conclusions: Proper early diagnosis with initial and adequate resuscitation is beneficial in having a good outcome in patients of BAT.